2011
DOI: 10.1371/journal.pone.0018343
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Burkholderia pseudomallei from a Remote Region of Papua New Guinea

Abstract: BackgroundThe island of New Guinea is located midway between the world's two major melioidosis endemic regions of Australia and Southeast Asia. Previous studies in Papua New Guinea have demonstrated autochthonous melioidosis in Balimo, Western province. In contrast to other regions of endemicity, isolates recovered from both environmental and clinical sources demonstrate narrow genetic diversity over large spatial and temporal scales.Methodology/Principal FindingsWe employed molecular typing techniques to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
2
21
1
1
Order By: Relevance
“…This ruggedness is especially true in the central region, where ST881 and ST997 were isolated. The apparent geographic restriction associated with limited sequence diversity of ST881 is similar to previous reports of B. pseudomallei isolates from Papua New Guinea, where low diversity of B. pseudomallei was observed in a geographically isolated region of Western Province (24,25). The narrow genetic variability within the majority of the Sarawak isolates and those from Papua New Guinea could potentially reflect recent but independent introduction events in those two locations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This ruggedness is especially true in the central region, where ST881 and ST997 were isolated. The apparent geographic restriction associated with limited sequence diversity of ST881 is similar to previous reports of B. pseudomallei isolates from Papua New Guinea, where low diversity of B. pseudomallei was observed in a geographically isolated region of Western Province (24,25). The narrow genetic variability within the majority of the Sarawak isolates and those from Papua New Guinea could potentially reflect recent but independent introduction events in those two locations.…”
Section: Resultssupporting
confidence: 85%
“…The narrow genetic variability within the majority of the Sarawak isolates and those from Papua New Guinea could potentially reflect recent but independent introduction events in those two locations. More likely, however, the observed overlap of certain STs in Malaysian Borneo with other Asian regions supports the hypothesis of a more ancient dispersal of B. pseudomallei to Malaysian Borneo, with dispersal and diversity in Sarawak restricted by its remoteness, and potentially also by limited anthropogenic activities (25).…”
Section: Resultsmentioning
confidence: 60%
“…The prevailing view of workers in the field is that strain lineages of B. pseudomallei possibly originated from Australia and subsequently spread to Southeast Asia and other regions [2,14]. Our results only suggest a link between B. pseudomallei from Thailand and China (Figs 3 and 4) but apart from ST562, no other ST was shared between strains from China and Australia.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, a lateral gene transfer event in the evolutionary history of B. pseudomallei has been identified which broadly conforms to these expectations; Australian isolates are more likely to encode the ancestral B. thailandensis-like flagellum and chemotaxis gene cluster (BTFC) while isolates from Asia almost exclusively carry a Yersinia-like fimbrial gene cluster (YLF) (13). We recently reported that isolates of B. pseudomallei from the Western Province of Papua New Guinea (PNG) are not only distinct by MLST but also demonstrate a narrow genetic diversity in contrast to isolates from mainland Australia (14), most likely resulting from longterm geographical separation. Together, these studies have indicated that B. pseudomallei dispersal occurs with relative ease over terra firma yet is hampered by relatively narrow passages of seawater, findings that mirror observations of macro flora and fauna.…”
supporting
confidence: 69%